Disease control after surgery for chronic rhinosinusitis: prospective, multi‐institutional validation of the Sinus Control Test. Issue 2 (26th July 2020) - Little, Ryan E.; Schlosser, Rodney J.; Smith, Timothy L.; Storck, Kristina A.; Alt, Jeremiah A.; Beswick, Daniel M.; Mace, Jess C.; Mattos, Jose L.; Ramakrishnan, Vijay R.; Soler, Zachary M.
Abstract : Background: The Sinus Control Test (SCT) is a 4‐question, patient‐reported questionnaire that assesses disease control in chronic rhinosinusitis (CRS). This prospective, multicenter study examines SCT outcomes following endoscopic sinus surgery (ESS), further validating its use as a control instrument for CRS. Methods: Adults with CRS undergoing ESS were prospectively enrolled from 5 centers across North America. The SCT was administered at baseline and once 6 months after surgery. Quality of life and disease burden were evaluated using the 22‐item Sino‐Nasal Outcome Test (SNOT‐22) and Lund‐Kennedy endoscopy scores. Linear regression was used to determine whether specific demographic, comorbidity, or disease severity measures were independently associated with changes in SCT scores postoperatively. Results: A total of 218 patients, 111 females (50.9%) and 107 males (49.1%), were enrolled, with mean ± standard deviation age of 50.1 ± 15.6 years. Mean SCT score improved from 8.9 ± 3.5 to 4.3 ± 3.7 postoperatively ( p < 0.001). Preoperatively, 21.6% were uncontrolled, 71.5% partially controlled, and 6.9% controlled. Postoperatively, 6.0% were uncontrolled, 42.6% partially controlled, and 51.4% controlled ( p < 0.001). Change in SCT score correlated independently with change in SNOT‐22 ( r = 0.500, p < 0.001) and endoscopy scores ( r = 0.310, p < 0.001). Endoscopy scores did not correlate with control status among patients with CRS without nasal polyposis (CRSsNP) nor between uncontrolled and partially controlled patients. Demographics and comorbidities were not associated with changes in SCT. Conclusion: Improvement in disease control following ESS as measured by the SCT correlated with improvements in SNOT‐22 and endoscopy scores. The SCT is an easily administered instrument that provides information complementary to existing patient‐reported and objective measures of disease severity.